The Influence of Authentic Leadership and Incentives Mediated by Job Satisfaction and Achievement Motivation towards the Enhancement of Continuous Professional Development - Ummami, Wage; Gistituati, Nurhizrah; ., Rifma; ., Hadiyanto; Marsyidin, Sufyarma (Journal of Ecohumanism, 2024)
Sustainable Personality Development is an important aspect that needs attention from various parties to enhance the teachers’ quality. Motivation for performance, work satisfaction incentives, and genuine leadership have an impact on continuous professional development. To understand its impact and identify the most dominant variables, a path analysis using SEM-PLS will be conducted. The research results have shown that job satisfaction incentives, authentic leadership, and achievement motivation directly influence continuous professional development. However, there is an unfulfilled direct effect, specifically the influence of genuine leadership on achievement motivation. This condition also applies to the indirect impact of genuine leadership on continuous professional development facilitated by achievement motivation.